Assessment of the Suitability of the One-Step Hydrothermal Method for Preparation of Non-Covalently/Covalently-Bonded TiO2/Graphene-Based Hybrids - Ewelina Kusiak-Nejman; Dariusz Moszyński; Joanna Kapica-Kozar; Agnieszka Wanag; Antoni W. Morawski (Nanomaterials, 2018)
A hybrid nanocomposites containing nanocrystalline TiO2 and graphene-related materials (graphene oxide or reduced graphene oxide) were successfully prepared by mechanical mixing and the hydrothermal method in the high-pressure atmosphere. The presented X-ray photoelectron spectroscopy (XPS) study and quantitative elemental analysis confirm similar content of carbon in graphene oxide GO (52 wt% and 46 wt%, respectively) and reduced graphene oxide rGO (92 wt% and 98 wt%, respectively). No chemical interactions between TiO2 and GO/rGO was found. TiO2 nanoparticles were loaded on GO or rGO flakes. However, Fourier transform infrared-diffuse reflection spectroscopy (FTIR/DRS) allowed finding peaks characteristic of GO and rGO. XPS study shows that since the concentration of TiO2 in the samples was no less than 95 wt%, it was assumed that the interactions between TiO2 and graphene should not influence the lower layers of titanium atoms in the TiO2 and they occurred as Ti4+ ions. Hydrothermal treatment at 200 °C did not cause the reduction of GO to rGO in TiO2-GO nanocomposites. In general, the one-step hydrothermal method must be considered to be inefficient for preparation of chemically-bonded composites synthesized from commercially available TiO2 and unfunctionalized graphene sheets obtained from graphite powder.